Predictors of treatment failure after top‐hat procedure in squamous intraepithelial lesion. Issue 2 (20th November 2020) - Chen, Xuhao; Fan, Birao; Jiang, Lu; Nong, Lin; Dong, Ying; Tao, Xia
Abstract: Aim: The value of top‐hat procedure during loop electrosurgical excision procedure (LEEP) for squamous intraepithelial lesions had remained controversial. This study aimed to evaluate whether top‐hat specimens positive for cervical intraepithelial neoplasia (CIN) on histopathology can serve as an independent risk factor to predict treatment failure. Methods: We reviewed the medical records of patients who underwent LEEP and top‐hat procedures in Peking University First Hospital between 2011 and 2016 and collected their follow‐up data until January 2019. We compared the pathological risk factor of treatment failure. Multivariate analysis was carried out to clarify the independent determinant of treatment failure. A Cox model was used to assess the influence of different variables on cumulative treatment failure rates. Results: This study included 295 cases for short‐term treatment failure, and among them, 178 cases were used to study the long‐term. The presence of CIN in top‐hat was relevant to short‐term treatment failure (OR = 9.64, 95% CI 2.55–36.4) despite a clear margin. On multivariate analysis, top‐hat result (OR = 3.58, 95% CI 1.30–9.89), age ≥ 50 (OR = 10.2, 95%CI 3.64–28.3) and post‐treatment HPV 16/18 infection (OR = 2.35, 95%CI 1.19–4.63) were independent risk factors in predicting short‐term failure. In the Cox model, these factors were also associated with higher cumulative failure rates. Conclusion: The current study supported the predictive value of top‐hat procedure in short‐term failure after LEEP. Typically, women with positive top‐hat need closer follow‐up despite their negative margin status. Older women with positive top‐hat findings and HPV 16/18 infections after the treatment suffer a higher risk of short‐term failure.